PERANCANGAN FITUR DARURAT DAN PENGINGAT PADA APLIKASI JAMAAH UMROH XYZ MENGGUNAKAN SCRUMBAN - Tiawan; Nusaibah; Rifky Kurniawan; Eliza Ariesta; Nilam Atsirina Krisnaputri; Amril Mutoi Siregar; Surjandy; Merios Gusan Putra; Dani Lukman Hakim; Samsul Arifin; Citra Nur Napiah (Program Studi Informatika Universitas Teknologi Sumbawa, 2026)
The problem of Umrah pilgrims getting lost and losing personal belongings is still common, especially in high-density areas such as the Grand Mosque and the Prophet's Mosque, with more than 50 cases of missing pilgrims per day during the peak Umrah season. A survey of 50 pilgrims showed that 86% of respondents experienced location disorientation and 74% had lost or nearly lost personal belongings. This study aims to design emergency and reminder features in the XYZ Umrah Pilgrim Application to improve security and management of pilgrim activities. The development method used is Scrumban, a combination of the iterative and structured Scrum method with the Kanban method that emphasizes workflow visualization and task management execution. The emergency feature is designed using the Fused Location Provider to send pilgrim location coordinates in real-time with a detection time of less than 30 seconds, while the reminder feature helps manage luggage and prayer schedules through a notification system. Functional and performance testing results show a feature success rate above 90%. The conclusion of this study shows that the integration of emergency and reminder features in one Umrah application with the Scrumban approach is able to improve the security and comfort aspects of the congregation.